Alar Flap Combined With Free Auricular Composite Flap for the Reconstruction of Nasal Alar Defect. Issue 2 (March 2015) - Lin, Wentao; Qing, Yong; Liu, Jia; Cen, Ying
<x xml:space="preserve">Abstract</x> Background The nasal ala plays an important role in the aesthetic appearance of the nose. Repairing the nasal alar defect, especially full-thickness alar defect, is one of the difficulties of plastic surgeons. In this article, a new surgical method is introduced about repairing full-thickness alar defect with free auricular composite flaps and local nasal alar rotation and advancement tissue flaps. Materials and Methods We retrospectively reviewed 6 patients with a diagnosis of full-thickness alar defect between 2010 and 2013. All of them accepted this new surgical method. The patients were followed up for 6 to 12 months. The method used local nasal alar rotation and advancement tissue flap to form new nasal rim and made the defect of nasal rim shift to alar groove region. After that, we harvested free auricular composite flap to repair the new defect. Result All patients attained relatively symmetrical nostrils with a natural, smooth, integrated alar rim and inconspicuous scars. All the reconstructed nasal alae were aesthetically satisfactory. Slight atrophy of grafts was observed in all patients. The shape of the donor ear changed a little. Two patients experienced hyperpigmentation change and one patient presented slight hypertrophic scar in the suture site. No other complications were observed. Conclusions This simple method not only reconstructed almost normal nasal alar rims and alar grooves but also improved the survival rate of the composite grafts without any free edges. This method also changed the traditional free auricular tissue flap location from the nasal alar rim to the upper alar groove region, which would help achieve more aesthetic appearance. This new method is a creative and useful technique for the repair of full-thickness alar defect.